Padrões de distribuição de pequenos mamíferos não voadores na Mata Atlântica - Alves, Kamila Souza (2013)
The Atlantic Forest, one of the most endangered ecosystems in the world, presents high species diversity and endemism. Despite its exceptional diversity, the fauna is still poorly known, especially concerning the most diversified groups, like Rodentia e Didelphimorphia. The lack of knowledge on taxonomy, known as the Linnaen Shortfall, is equally related to the factors that affect the distributional range of species occurring in this very heterogeneous biome, a fact defined as Wallacean Shortfall. Most studies aiming to understand the processes generating the distributional patterns of mammal species in the Atlantic Forest are concentrated on the effects of altitude. However, these studies are limited in scope, since they cover a minor scale, not contemplating the Atlantic Forest as a whole. In this work, we investigated the environmental factors that affect the nonvolant mammal species distribution in the Atlantic Forest of Brazil. The ideal framework to convey this endeavor was Macroecology, the subfield of ecology that deals with the study of relationships between organisms and their environment at large spatial scales to characterize and explain statistical patterns of abundance, distribution and diversity. The research was carried out at two taxonomic levels: genus and species. No general pattern was found when the analysis was conducted at the genus level, a result that can be attributed to niche conservatism, since this principle predicts that, in general, genera achieved their present distribution to factors other than the environmental ones, while at a species level the environmental cues are the main factors regulating the distribution patterns. The results pointed out that temperature seasonality was the main factor affecting the distributional pattern of non-volant small mammals in the Atlantic Forest. This result differs from the literature, a which indicate altitude as a major factor shaping distributional patterns of non-volant mammals in this biome. At last, we call attention on the high number of species recorded in the Dense Ombrophilous Forest, when compared to others ecoregions. This is another clue that reinforce the influence of seasonality on species iv distribution in the Atlantic Forest, since temperatures are more uniform, in these localities reflecting higher faunal richness in these phytophysionogmies.